Reforma al artículo 202 delito de “Receptación” del código orgánico integral penal por determinar la inconstitucionalidad relacionada al estado jurídico de inocencia - Ávila Silva, María Isabel (2015)
From the promulgation of the Constitution of the Republic of Ecuador, in the Official Gazette N ° 449, on 20 October 2008, our country is defined as a constitutional state of rights and justice. As stated is understood within the Supreme Charter of our Republic, reflected quite rightly principles, rights and guarantees that delimit the good development of the community found. I will initiate stating that between fundamental guarantees that contemplates the Inter-American Court of human rights, in article 8.2 establishes the principle of the presumption of innocence which, like our current Constitution of the Republic of the Ecuador, based on the eighth chapter, the rights of protection of the basic right to due guarantees, process, in its article 76 paragraph 2 stipulates: "The innocence of any person shall be presumed, and will be treated as such, while not declare its responsibility by enforceable judgement or firm resolution" The principle of innocence has as effect the right of the accused considered Treaty such as innocent and the duty of the other inhabitants and of the State to respect and not to violate in any way that State through expressions or resolutions that deem it prematurely guilty. It is thus that this principle does not determine the innocence of the accused with real meaning by the very fact of having started the process against her, but the imposition of constitutional guarantee their status and their legal status of innocent Even our Constitution of the Republic of Ecuador, determines that fade the status not with the mere fact of having a conviction, under the right to appeal to the ruling, Tine all accused in a criminal case, on a resolution that is considered unfavorable, but there must be a final judgement or enforceable to be able to lose the guarantee. The Feb. 10, 2014 is enacted through registry official number 180 the Integral Penal organic code, the same as after its "Vacatio legis" entered into force on 10 August 2014, legal body which as its name expresses integaria and repeal any law that verse about human behavior that injury legal property of third parties, and provide for criminal penaltie Well an example the law on Narcotic and psychotropic substances related to drug offences. Based on my research topic will discuss article 202 of organic comprehensive criminal code, "COIP" that with respect to the crime of receiving stolen goods, says: The person who hide, manage, store, transport, sells or transfers ownership, in whole or in part, of movable property, things or livestock to knowing that they are proceeds of theft, robbery or cattle rustling without documents or contracts to justify their ownership or possession, shall be punished with imprisonment from six months to two years. If by omission of the duty of care not made sure that the or the licensors of such documents or contracts are people whose data of identification or location can be established, shall be punished with a custodial sentence of two to six months. Type criminal simple reading determines the obligation to justify the ownership or possession of movable property, things or semimovientes, i.e. to demonstrate the legal provenance of these, being this preliminary determination to the accused in criminal proceedings, with what the procedural burden, would be reversed towards the innocent On the other hand within article 195 of the Constitution tells us "the Prosecutor's Office will lead, ex officio or upon request of a party, criminal procedural and pre-trial investigation; during the process, it will exert public action subject to the principles of opportunity and minimal criminal intervention, with special attention to the public interest and the rights of victims. Find worthwhile acknowledge the alleged offenders to the competent judge, and will boost the prosecution in the criminal trial proceedings" Indicating that the exercise of criminal action shall correspond to the State, through its official organ such as the Prosecutor's Office, responsible for breaking with the presumption of innocence Today the problem lies in the violation of the principle of State of innocence the principles of the State of innocence, specifically on the distribution of burden of proof in the criminal process (element derived from that principle), since the prosecution is in charge investigation, persecution and elucidation of the crimes but not the accused this does not have to prove his innocence since prior is constitutionally considered so, what happens with the article theme of reform, to indicate that it has to justify the holding of an asset with documents.